Development of perfectionism in junior athletes: Examination of actual and perceived parental perfectionism - Olsson, L. F.; Hill, A. P.; Madigan, D. J.; Woodley, G. (Journal of Sports Sciences, 2020)
Initial research suggests that parental perfectionism is central to the development of athlete perfectionism. However, it is unclear whether perceived or actual parental perfectionism is most important. The present study aimed to address this issue in two ways. First, we re-examined the predictive ability of actual versus perceived parental perfectionism on athlete perfectionism. Second, for the first time, we tested whether perceived parental perfectionism mediated the relationship between actual parental perfectionism and athlete perfectionism. A sample of 150 junior athletes and their parents completed measures of perfectionism (perfectionistic strivings and perfectionistic concerns). Junior athletes completed two measures, one of their own perfectionism and one of perceptions of their parents` perfectionism. Parents completed one measure of their own perfectionism. Regression analyses showed that perceived parental perfectionism predicted athlete perfectionism over and above actual parental perfectionism. Mediation analyses provided support for our proposed model. Overall, the findings suggest that both actual and perceived parental perfectionism are important in the development of perfectionism in junior athletes.